Kurt Cobain : the last interview and other conversations (Last interview series., 2022)
"Kurt Cobain's singing, songwriting, and guitar playing in his band Nirvana defined the soul of Generation X: fiercely caustic and passionate, but with an undercurrent of melancholy. By turns enigmatic, self-deprecating, acidic, and revealing, the conversations here--with three never published before, including one from just weeks before his tragic suicide--display Cobain at his most engaging and reflective. Whether he is talking about books, his peers in other bands, drugs, or the challenges of family life, these are the words of a man grappling with his inner demons and the pressures of fame." --Page [4] of cover.